Черная металлургия и металлообработка на территории междуречья Верхнего Прута и Среднего Днестра в Х – ХІІІ вв. - Возний, Ігор (Stratum plus. Культурная антропология. Археология., 2017)
I. P. Vozny Ferrous Metallurgy and Metalworking on the Territory between the Upper Prut and Middle Dniester Rivers in the 10th — 13th Centuries The article deals with the development of one of the leading sectors of ancient crafts, namely the ferrous metallurgy. The author analyzed iron-complexes on the territory between the Upper Prut and Middle Dniester, based on the characteristic of workshops related to the extraction and processing of bog ore, such as laminitis in Lenkovtsy, Chernovka, Klishkovtsy. It is postulated that the ore mining and iron production remained predominantly rural activity. One of the centers of iron processing was in Lenkovtsy on the Prut, where 16 “pitfalls” for firing ore were found. Iron-forges ground type, facilities, warehouses for storage of ball iron were revealed. The author analyzes workshops that processed pig iron, namely the blacksmith shops in Revno (10th century), Chernovka (12th — early 13th centuries.). Tools of blacksmiths and locksmiths are characterized and typology of household items related to the steel industry is offered.
Keywords: northern part of the area between the Prut and Dniester rivers; Old Russian period; metallurgy,; laminitis,; bloom,; pitfalls',; iron forge; craft shop,; blacksmith shop; instruments